PHARMACOLOGICAL EVALUATION OF LEVETIRACETAM AS ADD-ON DRUG TO EITHER PHENYTOIN OR SODIUM VALPROATE IN PATIENTS OF GENERALIZED ONSET TONIC-CLONIC SEIZURES HAVING BREAKTHROUGH SEIZURES: A RANDOMIZED AND COMPARATIVE STUDY - SAROJ KOTHARI; VINEET CHATURVEDI; AJAY GUPTA; DINESH UDAINIYA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Breakthrough seizures are sudden and unexpected seizures that occur in people with epilepsy who generally have good control over the symptoms. The present study is aimed to compare phenytoin plus levetiracetam versus sodium valproate plus levetiracetam to control breakthrough seizures. Methods: A prospective, comparative study was carried out in Generalized onset tonic-clonic seizures (GTCS) patients with breakthrough seizures in Gajra Raja Medical College, Gwalior (M.P.) from February 2021 to August 2022. Participants were randomly allocated to 2 groups, namely phenytoin + levetiracetam (PL) (n=62) and sodium valproate + levetiracetam (SL) (n=61). Patients in group PL received phenytoin at the dose of 200 mg twice a day in adults, 5 mg/kg/day in two divided doses in children plus levetiracetam 500 mg twice a day in adults and 30 mg/kg/day in three divided doses in children. Patients in group SL received sodium valproate 600 mg 3 times a day in adults, 30 mg/kg/day in three divided doses in children plus levetiracetam 500 mg twice a day in adults and 30 mg/kg/day in three divided doses in children. The mean reduction in seizure frequency and patients response to the treatment in the last 30 days were recorded before the start of therapy and at 3 and 6 months after therapy. Adverse drug reactions were recorded during the study period. Statistical analysis was performed using (Statistical Package for the Social Sciences) software. Results: Mean seizure frequency decreased by 59 and 85% in PL and by 59 and 91% in the SL group and is significant (p<0.05) from baseline value at 3 and 6 months, respectively, in both the groups. SL group showed significantly (p<0.05) better response, than PL group in controlling seizures at 6 months. Excellent response by patients was seen by 21% and 49% in PL and SL groups, respectively. Adverse effects noted during the study were mild, including somnolence, headache, dizziness, GIT stress, and fatigue, and responded to symptomatic treatment. Twenty-nine (29%) of PL cases and 6% of SL cases underwent fatigue as adverse drug reactions that showed better tolerability of the SL group. Conclusion: Sodium valproate plus levetiracetam is more efficacious and safer than phenytoin plus levetiracetam in the management of breakthrough seizures in GTCS patients.